PENYULUHAN PENCEGAHAN STUNTING PADA ANAK USIA DINI OLEH MAHASISWA KKN UMRI DI RW 07 KELURAHAN REJOSARI KOTA PEKANBARU - Nazhifah Nazhifah; Klarita Pitrusani Octavia Simamora; Fadhlan Hamidi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Stunting is the condition of infants and toddlers who have a smaller or shorter height than their age or can also be called stunted. Stunting results from chronic malnutrition and recurrent infections in children, especially during the 1,000 HPK period (First Day of Birth) (BPS, 2021). The latest data from the Ministry of Health shows that the stunting rate will reach 21.6% in 2022. Meanwhile, the figure set by the World Health Organization (WHO) as a standard for stunting rates is below 20%. Rejosari conducts outreach program activities regarding stunting prevention. From this activity, parents and prospective parents understand what stunting is and the right steps to avoid the causes of stunting that hinder the growth and development of their children.